The Influence of Marketing Mix 4p and Service Quality on Students’ Satisfaction at SMK Nusantara Weru, Cirebon District - Rahmiati, Ati; Suklani, Suklani; Duryat, Masduki (Journal of Social Work and Science Education, 2025)
In the midst of increasingly tight competition between educational institutions, schools are required to be able to maintain their existence by improving the quality of service and appropriate marketing strategies. Student satisfaction is an important indicator in assessing the success of educational institutions, including Vocational High Schools (SMK) which have a strategic role in producing competent and work-ready human resources. This study aims to analyze the effect of marketing mix and service quality on student satisfaction at SMK Nusantara Weru Cirebon, both partially and simultaneously. The method used is quantitative with a survey approach to 88 respondents, determined using the Slovin formula. The research instrument is a questionnaire that has been tested for validity and reliability. Data analysis was carried out through multiple linear regression using SPSS. The results of the study indicate that the marketing mix and service quality have a significant effect on student satisfaction. Simultaneously, the two variables explain 70% of the variation in student satisfaction, while the rest is influenced by other factors outside this study. These findings emphasize the importance of effective marketing strategies and improving service quality in increasing student satisfaction.